Turkey : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in Turkey during 1994-97. Real wages increased rapidly during 1989-93, dropped sharply in 1994-95, and have since recovered modestly. Real wage flexibility stems in part from the absence of widespread wage indexation, despite chronic high inflation. Rapid gross national product (GNP) growth, averaging 7.7 percent a year during 1995-97, raised GNP per capita to above USD 3,000 in 1997. Most of this dynamism originated from the industrial and trade sectors. Industry grew by 10.4 percent in 1997, led by a strong performance of private manufacturing (14.2 percent).